Linear growth of representatives of wheat seeds mycobiota - Tetiana Rozhkova; Lesia Golosna; Oksana Afanasieva; Liudmyla Nemerytska; Inna Zhuravska (Наукові горизонти, 2022)
Seed-born fungi of wheat interact with the plant at various stages of its development and with each other. With the highest growth rate, they should be isolated because of competition. The purpose of this study was to compare the growth of colonies on a nutrient medium for the gradation of fungal genera and species from wheat seeds according to aggressiveness. These data helped concluding on the effectiveness of mycoexpertise of winter wheat seeds. Potatoglucose agar (PGA) was used for the analysis of the fungal complex. Seven-day fungal cultures were sown in the centre of Petri dishes. Linear growth of fungal colonies on PGA with gentamicin was determined. The specific features of the development of 12 representatives of seeds mycobiota from the Northeast of Ukraine of the 2017-2019 harvest were investigated. The dominance of Alternaria sp. and a slight release of Fusarium sp. were established by analysis of the fungal complex. The first comparison of the linear growth of Fusarium graminearum, F. poae, and Alternaria tenuissima in 2017 showed that Fusarium colonies grow faster on nutrient medium. In 2018, the growth characteristics of A. arborescens, which quickly became dominant in wheat seeds mycoflora, and the littlecommon Trichothecium roseum were studied in detail. By comparing the growth of fast-growing F. graminearum with the common Aureobasidium pullulans and the aggressive Nigrospora oryzae, the fastest development of the third and the slowest of the second species was established. F. poae filled the Petri dish on day 6, Penicillium – on day 22. In 2019, in the first experiment comparing F. poae, F. sporotrichioides, and A. avenicola, the second species had the worst growth rates. It became the second fastest growing colony in the study of the growth of seven species in the second experiment. Isolates of N. oryzae in 2018 were more aggressive than in 2019. Specific features of colony growth on PGA did not affect the effectiveness of the analysis of mycobiota of winter wheat seeds. N. oryzae had the highest radial speed under the general dominance of Alternaria sp. Fusarium sp. (F. poae, F. sporotrichioides, F. verticillioides, and F. graminearum) and B. sorokiniana developed rapidly. A. arborescens and A. avenicola grew at the same level as A. pullulans. Penicillium and T. roseum lagged behind other fungi in speed and filled Petri dishes for the longest time. A. tenuissima had the lowest radial growth rate